Facing the challenges of the early 1990s (Commission of the European Communities LuxemborugLU, 1989)
Presents the Annual Economic Report 1989-90; a paper entitled The Community Economy at the turn of the decade; and analytical studies. The studies cover topics such as the recovery of growth in the 1980s and its main macroeconomic determinants; monetary policy indicators in an evolving monetary environment; public finances and fiscal policy in the Community; saving, investment and international financial markets: an overview; the effects of the internal market - sensitive sectors; and the Community as a world trade partner.
DC